Fraud Triangle dan Finansial Distress dengan Good Corporate Governance sebagai Variabel Moderating - Budhiyasa, Putu; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
This study aims to determine the effect of the fraud triangle on financial distress moderated by good corporate governance. The population in this study are state-owned companies listed on the Indonesia Stock Exchange in 2017-2020 as many as 20 companies. Sampling using purposive sampling, in order to obtain a sample of 13 companies. Data analysis used moderating regression analysis with the help of SPSS version 26 for windows. The results showed that pressure and opportunity had a significant positive effect on financial distress, while rationalization had no significant effect on financial distress. Good corporate governance is able to weaken the influence of pressure and opportunity on financial distress, while good corporate governance is not able to moderate the effect of rationalization on financial distress. Keywords: Financial Distress; Fraud Triangle; Good Corporate Governance.